Assessment of wind power potential at Hawksbay, Karachi Sindh, Pakistan - Shahnawaz Farhan Khahro; Amir Mahmood Soomro; Kavita Tabbassum; Lei Dong; Xiaozhong Liao (Institute of Advanced Engineering and Science, 2013)
Abstract Pakistan is facing serious energy crisis at present. The government is aiming to utilize the immense potential of renewable energy sources like: Solar, Wind, etc, in addition to intensify the conventional sources of energy to over the acute shortage of energy. Wind energy is the fastest-developing energy source worldwide. The aim of this paper is to explore and estimate the wind power potential of Hawksbay Karachi, one of the locations in southern part of Pakistan. Wind speed data (in meters per second) from April 2009 to April 2011 at four different heights is measured. Wind power densities, frequency distribution, and Weibull distribution of wind speed are calculated in this study. This study also presents the analysis and comparison of 5 numerical methods to determine the Weibull scale and shape parameters for the available wind data. The estimated wind power to be generated through commercial wind turbine is also included. The yearly mean wind speed at Hawksbay, Karachi is 5.9m/s and has power density of 197W/m2 at 80m height with high power density during April to August. The estimated cost per kWh is US0.0345. Therefore the site may be considered suitable for wind turbine applications. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2621